Complications of Diabetes Mellitus: A Systematic Review of Pathophysiological Mechanisms and Prevention Strategies - Aljohani, Najat; Aljohani, Ahmed; Alamir, Nabil Abdullah Yahya; Aljohani, Kamal Ahmed; Hassan, Hamood Mohammed; Allaf, Saleh Mowafag; Almkeel, Mahdi Shatwai; Al jarah, Mohammed Hussain Ali; Alasiri, Omar Ahmed; Al-Muzaibi, Maqbool Ahmed (Journal of Posthumanism, 2024)
Diabetes mellitus (DM) is a complex metabolic disorder characterized by chronic hyperglycemia leading to multiple microvascular and macrovascular complications. This systematic review examines the underlying pathophysiological mechanisms contributing to diabetic complications and evaluates current prevention and management strategies. Peer-reviewed studies published between 2016 and 2025 were analyzed using PRISMA guidelines. Major complications—including neuropathy, nephropathy, retinopathy, and cardiovascular disease—were explored in relation to oxidative stress, advanced glycation end-products (AGEs), inflammation, and endothelial dysfunction. Preventive approaches such as lifestyle modification, pharmacological interventions, and emerging technologies like continuous glucose monitoring and AI-driven insulin delivery were also evaluated. Findings reveal that early diagnosis, integrated care models, and personalized therapies significantly reduce complication risk. This review highlights the need for multidisciplinary management and advances in molecular research to mitigate diabetes-related morbidity and mortality.